Pemanfaatan Tawas sebagai Sediaan Antiperspiran dan Pasca-Cukur - Haerani, Ani; Apriliana, Putri; Apriliani, Cindy Putri; Nuraeni, Euis; Astuti, Anggi Dwi (Jurnal Kesehatan Rajawali, 2024)
Body odor in humans usually occurs due to the overproduction of sweat glands and the presence of bacteria. Antiperspirants are cosmetic preparations that are used to restrain the release of excessive amounts of sweat by narrowing the pores of the sweat glands, both eccrine and apocrine. This study aims to make deodorant spray/stick/stick preparations by utilizing natural ingredients, namely alum. In this study, several tests were used including organoleptic tests, irritation tests, pH tests, melting time tests, melting point tests, and antiperspirant tests. Alum powder has wide traditional use as an astringent to prevent bleeding from minor wounds and promote their healing. Therefore, dosage forms are more precisely designed with suitable concentrations (2% gel) to extend their astringent activity with higher retention times due to the highly viscous nature of the gel. Using suitable excipients, 2% lotions and gels were prepared by the dispersion method while emulsifiers were used for the preparation of potassium alum cream of equal strength. The research results obtained were homogeneous, did not cause irritation to the skin, yellowish green in color and showed no change in the formulation which showed its stability as a dosage form and its size as a commercial product line.